Scoring English Proficiency Through Englishscore - Ira Irzawati; Agnes Felisya Unamo; Sopian Sopian (FKIP, Universitas Palangka Raya, 2025)
This descriptive research aims to shed light the general portrait of the utilization of EnglishScore as an international standardized test. It also intends to describe the test takers’ insights on the use of EnglishScore application. Eighty-two participants involved in this study. Questionnaire was employed to collect the data. The data were analyzed by Miles, et al Model consisting of collection, classification, description, and conclusion. The results imply that EnglishScore is an ideal and innovative English test and it is valid to use to measure the test takers’ English proficiency level since it is aligned with CEFR. Thus, it facilitates a better understanding and achievement of the test takers’ English proficiency.